Graphene-based nanolaminates as ultra-high permeation barriers. (December 2017) - Sagade, Abhay; Aria, Adrianus; Edge, Steven; Melgari, Paolo; Gieseking, Bjoern; Bayer, Bernhard; Meyer, Jannik; Bird, David; Brewer, Paul; Hofmann, Stephan
Abstract Permeation barrier films are critical to a wide range of applications. In particular, for organic electronics and photovoltaics not only ultra-low permeation values are required but also optical transparency. A laminate structure thereby allows synergistic effects between different materials. Here, we report on a combination of chemical vapor deposition (CVD) and atomic layer deposition (ALD) to create in scalable fashion few-layer graphene/aluminium oxide-based nanolaminates. The resulting ~10 nm contiguous, flexible graphene-based films are >90% optically transparent and show water vapor transmission rates below 7 × 10−3  g/m2 /day measured over areas of 5 × 5 cm2 . We deploy these films to provide effective encapsulation for organic light-emitting diodes (OLEDs) with measured half-life times of 880 h in ambient. Nanofabrication: synergistically produced graphene/AlOx nanolaminates are efficient permeation barrier layers A combination of chemical vapor deposition and atomic layer deposition enables laminated structures of graphene and aluminium oxide (AlOx ). A team led by Stephan Hofmann at the University of Cambridge devised a fabrication route to create in scalable fashion few-layer graphene/AlOx -based nanolaminates. The resulting hybrid films are nanometer-thick, are bendable, and offer 90% optical transparency. Compared to sequential layering of graphene and AlOx films by means of standard transfer techniques, these nanolaminates provide significantly lower water vapor transfer rates while offering reproducible performance as moisture barrier films over large areas. The introduced layer structure can be used as repeat layer unit or as part of a further multi-layer structure analogue to current much thicker commercial barrier films. The team demonstrated that the nanolaminate can be effectively integrated in organic light emitting diodes (OLEDs), enabling half-life times of 880 h in ambient. These results highlight the potential of such nanolaminates as building block to engineer new functionalities and form factors for flexible and wearable technology.